Pengaruh Pengalaman Kerja Dan Jenjang Pendidikan Terhadap Fresh Graduate Di Surabaya - Ardi Armadani; Dheraya Ananda DwiNov; Vizenchia Millian Letlora; Nindya Kartika Kusmayati; Taufik Kurniawan (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2025)
This research aims to determine whether work experience and education level have an impact on the job readiness of fresh graduates in Surabaya. The main focus of this research is the challenges that fresh graduates will face when entering the workforce, where work experience and educational background often become factors to consider in the recruitment process. The approach we used in this research is quantitative, with data collection methods carried out through the distribution of questionnaires to fresh graduates in the city of Surabaya. The collected data were analyzed using multiple linear regression techniques to see whether the influence of the two independent variables, both simultaneously and partially, on the dependent variable. The results of the analysis show that work experience and educational level significantly and positively affect the job readiness of new graduates. However, individually, work experience contributes more significantly compared to the level of education. In this case, it can be shown that companies in the city of Surabaya place more emphasis on the practical aspects possessed by candidates. This research is expected to provide an overview for new graduates in preparing themselves to enter the workforce, as well as serve as input for educational institutions in designing curricula that align with the current needs of the industry.